2013
DOI: 10.1111/tpj.12152
|View full text |Cite
|
Sign up to set email alerts
|

The jasmonic acid signaling pathway is linked to auxin homeostasis through the modulation of YUCCA8 and YUCCA9 gene expression

Abstract: SUMMARY Interactions between phytohormones play important roles in the regulation of plant growth and development, but knowledge of the networks controlling hormonal relationships, such as between oxylipins and auxins, is just emerging. Here, we report the transcriptional regulation of two Arabidopsis YUCCA genes, YUC8 and YUC9, by oxylipins. Similarly to previously characterized YUCCA family members, we show that both YUC8 and YUC9 are involved in auxin biosynthesis, as demonstrated by the increased auxin con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
176
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(194 citation statements)
references
References 78 publications
(127 reference statements)
15
176
0
3
Order By: Relevance
“…We confirmed this by removing leaf blades, which resulted in inhibition of regeneration. YUC9 expression has been shown to respond to methyl-jasmonate (MeJA) treatment in a COI1-dependent manner (Hentrich et al, 2013). As excision of whole leaves or leaf blades involves wounding and therefore MeJA production, MeJA might activate YUC9 expression to rapid increase auxin levels in leaf blades, likely in combination with YUC1 and YUC4 activity.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed this by removing leaf blades, which resulted in inhibition of regeneration. YUC9 expression has been shown to respond to methyl-jasmonate (MeJA) treatment in a COI1-dependent manner (Hentrich et al, 2013). As excision of whole leaves or leaf blades involves wounding and therefore MeJA production, MeJA might activate YUC9 expression to rapid increase auxin levels in leaf blades, likely in combination with YUC1 and YUC4 activity.…”
Section: Vasculature Proliferation and Endogenous Callus Formationmentioning
confidence: 99%
“…The reporter lines Pro IPT3 :GUS, Pro IPT5 :GUS (Miyawaki et al, 2004), Pro LOG4 :GUS s (Kuroha et al, 2009) obtained from RIKEN, and Pro ARR5 :GUS (D' Agostino et al, 2000) were used for tracing cytokinin biosynthesis and signaling during rooting. Pro YUC8 :GUS, Pro YUC9 :GUS (Hentrich et al, 2013) and Pro DR5 :GUS (Ulmasov et al, 1997) were used to investigate auxin biosynthesis and signaling; Pro PIN3 : PIN3:GFP (Xu et al, 2006) and Pro PIN4 :GUS (Friml et al, 2004) were used for auxin transport. To trace the molecular mechanisms during de novo root formation we used: Pro WIND1 :GUS (Iwase et al, 2011), Pro WOX11 :GUS , Pro WOX5 :GUS (Sarkar et al, 2007), and Pro SKP2Bs :GUS (Manzano et al, 2012), which corresponds to a promoter deletion containing 0.5 Kb upstream from the ATG.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Endogenous Auxin Overproduction Partially Rescued smo2-1 smo2-2 Embryonic Lethality and Fully Rescued smo2-1 smo2-2/+ Mutant Phenotypes Previous studies in Arabidopsis have indicated that YUC9 OE contributes to the overproduction of free IAA (Hentrich et al, 2013). To examine the effects of endogenously overproduced auxin on smo2 double mutants, we crossed YUC9 OE transgenic plants with smo2-1/+ smo2-2 and smo2-1 smo2-2/+ mutants.…”
Section: -E)mentioning
confidence: 99%
“…In A. thaliana, JAMe inhibits primary root elongation via stimulation of YUC8 and YUC9 expression involved in auxin biosynthesis [33]. Gutierrez et al [34] proposed that auxin, through the positive regulators ARF6 and ARF8, induces the formation of adventitious roots by stimulating the expression of auxin-inducible genes encoding acyl-acid-amido synthetases (GH3.3, GH3.5, and GH3.6), consequently causing JA conjugation and reduction the level of free JA.…”
Section: Introductionmentioning
confidence: 99%